Peran Empati untuk Meningkatkan Kepuasan Mahasiswa Universitas Andalas Kampus Payakumbuh - Lukman, Lukman; Yindrizal, Yindrizal; Susiana, Susiana; Graha, Fager Van; Zahra, Melkia (Program Pascasarjana STIE Amkop Makassar, 2024)
The background of this study aims to determine the role of empathy in increasing student satisfaction as customers at Andalas University, Payakumbuh Campus. The programs at Andalas University, Payakumbuh Campus are competitive, so it is important to understand the role of empathy in increasing customer satisfaction. This study uses a qualitative approach and the population of this study consists of students who study at Andalas University, Payakumbuh Campus for at least 1 year. Empathy is considered an important factor in building relationships between service providers and customers because it provides a better understanding of customer feelings and needs. This study is a qualitative study and data analysis was conducted on informants who received services at Andalas University, Payakumbuh Campus, so that the relationship between the level of empathy received from service providers and customer satisfaction can be known. The results of the analysis show that there is a positive relationship between a high level of empathy from service providers and customer satisfaction at Andalas University, Payakumbuh Campus. Customers who feel understood by their service providers are more likely and satisfied with the overall service quality. This study also shows factors that influence the level of empathy from service providers, including the development of relationships between staff training and organizational culture that supports critical thinking. The results of this study are useful for service management in developing strategies to increase the level of empathy of service providers at Andalas University, Payakumbuh Campus. With increased empathy, customers of Andalas University, Payakumbuh Campus will feel more appreciated and have a positive impact on customer satisfaction.